The effect of amylase, chromium propionate and their combination supplementation on growth performance, carcass traits, serum parameters, antioxidant capacity and intestinal health in yellow feathered broilers - Kun Chen; Junran Lv; Zheng Luo; Zhuang Liu; Mingzhu Cen; Benkuan Li; Jiancun Ou; Huihua Zhang (Poultry Science)
To better understand the growth promotion mechanism of amylase and chromium propionate (Cr Prop) and assess their potential synergistic effects, a total of 640 one-day-old male yellow-feathered broilers were randomly allocated to four dietary treatments with eight replicates. The birds were fed either a basal diet or the basal diet supplemented with amylase, Cr Prop or a combination of both. The results showed that during the grower, finisher and overall phases, average daily feed intake, final body weight, and feed conversion ratio were significantly improved (P < 0.05) in the amylase and Cr Prop treatment groups. However, no significant differences (P > 0.05) were observed in carcass traits. Amylase supplementation alone significantly reduced breast muscle drip loss (P < 0.05). Amylase supplementation significantly increased (P < 0.05) the concentration of glutathione peroxidase in breast muscle and plasma, as well as catalase in breast muscle, while it decreased (P < 0.05) catalase in the liver and malondialdehyde in breast muscle. Supplementation with Cr Prop significantly elevated (P < 0.05) the concentration of glutathione peroxidase in the liver and plasma, as well as the concentration of total superoxide dismutase in the liver, while it reduced (P < 0.05). the concentration of malondialdehyde in breast muscle. Supplementation with either amylase or Cr Prop significantly increased (P < 0.05) the levels of blood high-density lipoprotein cholesterol, immunoglobulin A, immunoglobulin G, and total protein, while significantly reducing (P < 0.05) triglyceride levels. Amylase supplementation alone notably enhanced villus height in both the jejunum and ileum. Furthermore, amylase or Cr Prop significantly upregulated (P < 0.05) the mRNA expression of Occludin and Claudin-1 in the Jejunum. The expression of Zona Occluden-1 was elevated by Cr Prop. However, the expression of Mucin 2 and Zona Occluden-2 remained unaffected. While amylase or Cr Prop supplementation alone could improve the performance and several healthy parameters in yellow-feathered broilers, no synergistic effect was observed.